Effects of an 11-week vibro-tactile stimulation treatment on voice symptoms in laryngeal dystonia - Konczak, Jürgen; Bhaskaran, Divya; Elangovan, Naveen; Oh, Jinseok; Goding, George S.; Watson, Peter J. (Frontiers in Neurology, 2024)
Background Laryngeal dystonia is a task-specific focal dystonia of laryngeal muscles that impairs speech and voice production. At present, there is no cure for LD. The most common therapeutic option for patients with LD involves Botulinum neurotoxin injections. Objective Provide empirical evidence that non-invasive vibro-tactile stimulation (VTS) of the skin over the voice box can provide symptom relief to those affected by LD. Methods Single-group 11-week randomized controlled trial with a crossover between two dosages (20 min of VTS once or 3 times per week) self-administered in-home in two 4-week blocks. Acute effects of VTS on voice and speech were assessed in-lab at weeks 1, 6 and 11. Participants were randomized to receive either 40 Hz or 100 Hz VTS. Main outcome measures Primary: smoothed cepstral peak prominence (CPPS) of the voice signal to quantify voice and speech abnormalities, and perceived speech effort (PSE) ranked by participants as a measure of voice effort (scale 1–10). Secondary: number of voice breaks during continuous speech, the Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V) inventory as a measure of overall disease severity and the Voice Handicap Index 30-item self report. Results Thirty-nine people with a confirmed diagnosis of adductor-type LD (mean [SD] age, 60.3 [11.3] years; 18 women and 21 men) completed the study. A single application of VTS improved voice quality (median CPPS increase: 0.41 dB, 95% CI [0.20, 0.61]) and/or reduced voice effort (PSE) by at least 30% in up to 57% of participants across the three study visits. Effects lasted from less than 30 min to several days. There was no effect of dosage and no evidence that the acute therapeutic effects of VTS increased or decreased longitudinally over the 11-week study period. Both 100 and 40 Hz VTS induced measurable improvements in voice quality and speech effort. VTS induced an additional benefit to those receiving Botulinum toxin. Participants, not receiving Botulinum treatment also responded to VTS. Conclusion This study provides the first systematic empirical evidence that the prolonged use of laryngeal VTS can induce repeatable acute improvements in voice quality and reductions of voice effort in LD. Clinical trial registration ClinicalTrials.gov ID: NCT03746509.